2008
DOI: 10.1242/dev.024380
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis ofDrosophilaantennal lobe neurons: diverse neuronal architectures in the lateral neuroblast lineage

Abstract: The antennal lobe (AL) is the primary structure in the Drosophila brain that relays odor information from the antennae to higher brain centers. The characterization of uniglomerular projection neurons (PNs) and some local interneurons has facilitated our understanding of olfaction; however, many other AL neurons remain unidentified. Because neuron types are mostly specified by lineage and temporal origins, we use the MARCM techniques with a set of enhancer-trap GAL4 lines to perform systematical lineage analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
267
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(282 citation statements)
references
References 61 publications
13
267
2
Order By: Relevance
“…The UAS-dPQBP1 transgenic fly, carrying a 0.7 kb full-length cDNA of CG11820 on the second chromosome was developed from w1118 parental strain. GH146-LexA::GAD (LG-GH146) and LexAop-GFP fly stocks were previously described (Lai et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The UAS-dPQBP1 transgenic fly, carrying a 0.7 kb full-length cDNA of CG11820 on the second chromosome was developed from w1118 parental strain. GH146-LexA::GAD (LG-GH146) and LexAop-GFP fly stocks were previously described (Lai et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the processes of 1300 ORNs and 200 PNs, the antennal lobe also contains neurites from 200 local interneurons (LNs) (Das et al 2008;Lai et al 2008;Okada et al 2009;Chou et al 2010a). LNs make connections with both ORN axons and PN dendrites and play important roles in ORN-to-PN information transformation (Wilson 2013).…”
Section: Local Interneuronsmentioning
confidence: 99%
“…Thus Acj6 and Drifter are required for the specification of dendrite targeting of ad-and l-PNs, respectively. However, recent findings revealed that Acj6 is also expressed in some atypical PNs in l-lineage (Lai et al, 2008;Lin et al, 2012), suggesting that the targeting specification by Acj6 is limited inside uniglomerular PNs. Inside lineages, the birth order strictly dictates the fate of each postmitotic neuron.…”
Section: Specification Of Pnsmentioning
confidence: 99%
“…Thus the fate of individual neurons in the ad-PN lineage is tightly regulated on the basis of the time window of their birth. Another study showed that the birth order is also important in l-and v-lineages that produce not only PNs but also other types of neurons, such as LNs (Lai et al, 2008;Lin et al, 2012). To ensure the temporal specification of the types of neurons, various transcription factors can also be sequentially and transiently expressed in neuroblasts that produce PNs, since the transcription factor cascade (early to late: Hunchback → Krüppel → Pdm → Castor) is known to specify the first several neurons across neuroblast lineages in the embryonic ventral nerve cord (Isshiki et al, 2001).…”
Section: Specification Of Pnsmentioning
confidence: 99%
See 1 more Smart Citation